2021
DOI: 10.1101/2020.12.31.424868
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Canonical features of human antibodies recognizing the influenza hemagglutinin trimer interface

Abstract: SUMMARYBroadly reactive antibodies targeting the influenza A hemagglutinin (HA) head domain are thought to be rare and to require extensive somatic mutations or unusual structural features to achieve breadth against divergent HA subtypes. Here we describe common genetic and structural features of diverse human antibodies from several individuals recognizing the trimer interface (TI) of the influenza HA head, a recently identified site of vulnerability1–3. We examined the sequence of TI-reactive antibodies, det… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Uncleaved HA ectodomain (HA0) is monomeric and does not induce significant amounts of neutralizing antibodies. Although several antibodies that recognize the trimer interface have been described, suggesting some degree of reversible "breathing" of the HA trimer apex (3)(4)(5)(6), the cleaved HA at the viral surface is predominantly in a closed trimeric conformation (7)(8)(9). For all current vaccines and emerging recombinant vaccine vectors or nucleic acid vaccines (10), the delivery of a conformationally correct prefusion HA trimer with improved expression, quality, and stability is crucial (11).…”
mentioning
confidence: 99%
“…Uncleaved HA ectodomain (HA0) is monomeric and does not induce significant amounts of neutralizing antibodies. Although several antibodies that recognize the trimer interface have been described, suggesting some degree of reversible "breathing" of the HA trimer apex (3)(4)(5)(6), the cleaved HA at the viral surface is predominantly in a closed trimeric conformation (7)(8)(9). For all current vaccines and emerging recombinant vaccine vectors or nucleic acid vaccines (10), the delivery of a conformationally correct prefusion HA trimer with improved expression, quality, and stability is crucial (11).…”
mentioning
confidence: 99%
“…The continued investigation into identifying protective epitopes using mAbs as we have done here may inform future structurebased rational design of next-generation SARS-CoV-2 vaccines by revealing protective sites whose structure should be preserved in engineered vaccine antigens. Most potently neutralizing SARS-CoV-2 mAbs discovered to date recognize the RBD region, while some moderately neutralizing NTD-directed mAbs also were identified Baum et al, 2020;Cerutti et al, 2021b;Chen et al, 2021b;Chi et al, 2020;Dong et al, 2021;Hansen et al, 2020;McCallum et al, 2021;Pinto et al, 2020;Rogers et al, 2020;Shi et al, 2020;Suryadevara et al, 2021;Turner et al, 2021c;Zost et al, 2020a). All of the NTD-reactive mAbs reported to date have lost their neutralizing capacity against certain emerging VOC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently several reports about mAbs targeting the trimer interface of multiple viral antigens have been published. For instance, the non-neutralizing influenza mAbs FluA20 and 5J6 that recognize the hemagglutinin trimer interface (Bangaru et al, 2019;Zost et al, 2021) were identified from influenza-vaccinated individuals. Also, epitope mapping using polyclonal serum from vaccinated rabbits identified antibodies recognizing the HIV envelope glycoprotein trimer interface (Turner et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, public B cell clonotypes have been identified in the human antibody repertoires formed in response to diverse viruses including Ebola [18][19][20] , influenza [21][22][23][24][25] , human immunodeficiency virus 1 (HIV-1) [26][27][28][29] , hepatitis C 30,31 , SARS-CoV-2 [32][33][34] , and in healthy individuals 35,36 . These studies reveal a convergence of B cell selection resulting in circulating B cells clones with genetically similar antigen receptor genes in multiple individuals.…”
Section: Introductionmentioning
confidence: 99%